COMBINED EFFECT OF GLYPHOSATE, SACCHARIN AND SODIUM BENZOATE ON THE GUT MICROBIOTA IN RATS - Bilan, M.V.; Brygadyrenko, V.V.; Lieshchova, M.A.; Tishkina, N.M. (World of Medicine and Biology, 2019)
In a laboratory experiment on adult white rats, it has been determined that addition of glyphosate, as well as glyphosate in a mixture with saccharin, to the diet contributes to broader reproduction of microorganisms of the Klebsiella, Citrobacter, Enterobacter and Pseudomonas genera. Mixtures of glyphosate and food additives allow conditionally pathogenic yeast-like Candida fungi (Candida glabrata and C. albicans) to spread more widely in the intestine. Significant fluctuations in the number of Enterococcus spp. bacteria genus were observed: by 108 times within range of each of the three experimental groups of rats with addition of herbicide with benzoate and saccharin to the diet.
Keywords: gut microbiota; glyphosate; herbicides; saccharin; benzoate